How do patients from South Asian backgrounds experience life on haemodialysis in the UK? A multicentre qualitative study. Issue 5 (16th May 2019) - Sharma, Shivani; King, Madeline; Mooney, Roisin; Davenport, Andrew; Day, Clara; Duncan, Neill; Modi, Kirit; Da Silva-Gane, Maria; Wellsted, David; Farrington, Ken
Abstract : Objectives: End-stage kidney disease disproportionately affects people of South Asian origin. This study aimed to uncover the lived experiences of this group of patients on centre-based haemodialysis (HD), the most prevalent dialysis modality. Design: The study utilised a qualitative focus group methodology. Seven focus groups were conducted across four NHS Trusts in the UK including three in Gujarati and two each in Punjabi and Urdu. This provided an inclusive opportunity for South Asian patients to contribute in their language of origin. A total of 24 patients participated. Focus groups were facilitated by bilingual project workers and data were forward translated and analysed using thematic analysis. Results: Four themes were identified. This included (1) 'treatment imposition', which comprised of the restrictive nature of HD, the effects of treatment and the feeling of being trapped in an endless process. (2) The 'patient–clinician relationship' centred around the impact of a perceived lack of staff time, and inadequacies in the quality of interactions. (3) 'Coping strategies' highlighted the role of cognitive reappraisal, living in the moment and family support networks in facilitating adjustment. (4) 'Pursuit of transplantation' included equating this form of treatment with restoring normality, alongside cultural factors limiting hopefulness for receiving an organ. Conclusions: In general, the experiences of South Asian patients receiving HD were not unique to this ethnic group. We did find distinct issues in relation to interactions with healthcare professionals, views on access to transplantation and the importance of family support networks. The study provides useful insights which may help enhance culturally tailored renal care.